Segunda restauración de Bursera ovalifolia y nombre nuevo para otro componente del complejo de B. simaruba (Burseraceae) - Rzedowski, Jerzy; Medina Lemos, Rosalinda; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2007)
One of the taxonomically most difficult groups of the genus Bursera centers around B. simaruba. Several members of this group are often difficult to distinguish from each other and from the very variable B. simaruba.In 1936 Bullock reduced several of these components to synonymy under B. ovalifolia (Schltdl.) Engl., because he considered that the proper B. simaruba, the type of which comes from Jamaica, does not exist in Mexico. Later studies, however, showed that many Mexican populations are similar enough to the West Indian plants to be considered members of the same species. Consequently Schlechtendal’s epithet became abandoned.In this contribution B. ovalifolia is reinstated for a species characterized by relatively small fruits and leaves with 3 or 5 (rarely 7) leaflets with an abruptly acuminate or cuspidate apex, glabrous or scarcely pubescent, even in their expansion. Its distribution ranges from coastal Jalisco at least to Costa Rica and the trees are particularly abundant in the Oaxacan region of the Tehuantepec Isthmus, where a great diversity of leaflet forms can be observed.On the other hand, the name B. roseana is proposed for another member of this group, originally described as Terebinthus acuminata, but never legitimately transferred to the genus Bursera. This species grows essentially at altitudes of more than 1200 m, often cohabiting with oaks and pines, and ranging from Nayarit, Zacatecas and Aguascalientes to the State of Mexico and Guerrero.